Foreign languages and employability: a complex relationship. Case study in the region of Viseu (Portugal) - Delplancq, Véronique (2018)
The challenges of today's societies when it comes to employability and to the reality of the current labour market are more and more delicate and diversified. One of the major commitments we expect from higher education is to prepare its students to face this kind of complexity, understanding its nuances and having the capacity to adapt quickly to situations which are common in companies’ lives. From this perspective, the assessment of the impact that the mastery of FL (foreign languages) among our students can have on the different business sectors becomes paramount. It involves reorganising the work carried out with the students during their academic path and raising awareness of future professionals so they may understand the importance of obtaining and mastering communicative skills in foreign languages that will provide them with the right tools to ensure an effective response to the requirements they will have to meet when they apply for a job. The close connection that exists between higher education institutions and the business world also allows the companies to realize that they should (re)think their recruitment policy in order to take into account the importance of foreign languages. Bearing this in mind, the project "Foreign Languages and Employability" (FLE), that will be presented in this article, started in January 2017, at the Polytechnic Institute of Viseu (IPV), in Portugal. It focuses on creating a closer relationship with the local business community in order to understand its needs regarding foreign languages. The aim of the project is to strengthen the more practical aspects of the students’ education to ensure the graduates’ employability and a successful professional development. Data collection is carried out through the analysis of job offers, through the replies given to online surveys and through semi-structured interviews. The project includes representatives of the different IPV schools (Agrarian, Education, Health, Technology and Management) working in different sectors of the institution.